n-type SnS thin film, photoelectric conversion element, solar cell, method for producing n-type SnS thin film, and apparatus for producing n-type SnS thin film

JP7651104B2Active Publication Date: 2025-03-26TOHOKU UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2020108143
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-23
Publication Date
2025-03-26
Estimated Expiration
2040-06-23

Smart Images

  • Figure 0007651104000002
    Figure 0007651104000002
  • Figure 0007651104000003
    Figure 0007651104000003
  • Figure 0007651104000001
    Figure 0007651104000001
Patent Text Reader

Abstract

To provide an n-type SnS thin film with high impurity activation rate and n-type conductivity.SOLUTION: An n-type SnS thin film has a thickness of 0.100 μm to 10 μm, the ratio (α1.1 / α1.6) of the absorption coefficient α1.1 at photon energy of 1.1 eV to the absorption coefficient α1.6 at photon energy of 1.6 eV of equal to or less than 0.200, the atomic ratio of S content to Sn content (S / Sn) of 0.85 to 1.10, and n-type conductivity.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an n-type SnS thin film, a photoelectric conversion element, a solar cell, a method for producing an n-type SnS thin film, and an apparatus for producing an n-type SnS thin film. [Background technology]

[0002] Currently, solar cells are widely used, but in order to further popularize them, it is necessary to reduce manufacturing costs and increase efficiency. To achieve this, it is necessary to develop new mechanisms and low-cost materials and processes that achieve high efficiency.

[0003] Suitable photovoltaic cell materials for achieving high efficiency include, for example, GaAs, Cu(In,Ga)Se2 (CIGS), and CdTe, but GaAs has the problem of containing the rare metal Ga and the harmful element As, and CIGS has the problem of containing the rare metals In and Ga. Furthermore, CdTe has the problem of containing the rare element Te and the harmful element Cd.

[0004] SnS is an example of a material for solar cells that is less harmful and has low raw material costs. Furthermore, SnS has a direct gap of 1.3 eV, an indirect gap of 1.1 eV, and a theoretical limit conversion efficiency of over 30%. SnS has a light absorption coefficient α of 10 at 2 eV. 5 cm -1 For the above reasons, a thickness of about 2 to 3 μm is sufficient to absorb light. In addition, SnS has the advantage that a thin film can be formed using a general-purpose process.

[0005] Since there is no n-type SnS thin film, the SnS solar cells that have been fabricated so far have mainly been heterojunction solar cells that use other semiconductor thin films (such as CdS thin film) in the n-type layer. The conversion efficiency of SnS solar cells fabricated so far has been 4.4%, which is much lower than the theoretical limit conversion efficiency. This is because conventional SnS solar cells use a heterojunction in which the p-type and n-type semiconductors are made of different materials. In the case of a heterojunction, the offset (ΔE) between the energy at the top of the valence band of the p-type semiconductor and the energy at the bottom of the conduction band of the n-type semiconductor at the interface is an indication of the voltage that can be extracted. However, since the energy at the bottom of the conduction band of SnS is high, in the case of a heterojunction, ΔE is relatively small, so the open voltage is low and the conversion efficiency is low. For example, the open voltage of a CIGS solar cell consisting of a heterojunction of CIGS and CdS is 700mV, while the open voltage of a SnS solar cell consisting of a heterojunction of SnS and CdS is 200mV. If an n-type SnS thin film can be obtained, a homo pn junction using SnS for both the p-type and n-type layers can be realized, and it is expected that a highly efficient solar cell can be obtained by improving the open circuit voltage.

[0006] For SnS, the vapor pressure of S (vapor pressure at 500°C: 4×10 5 Pa) is the vapor pressure of Sn (vapor pressure at 500°C: 1×10 -6 Since the thermal stress is much higher than the thermal stress at the interface between the two materials (Pa), SnS has the problem of being prone to defects in which Sn occupies sites that should be occupied by S. When such defects are present, holes are generated to maintain electrical neutrality, and SnS tends to become a p-type semiconductor.

[0007] As n-type SnS, Patent Document 1 discloses n-type SnS in which Br is added to SnS (tin sulfide). Non-Patent Document 1 discloses an n-type SnS thin film in which Pb is added to SnS. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2019-178012 A [Non-patent literature]

[0009] [Non-Patent Document 1] Fan-Yong Ran et al. n-type conversion of SnS by isovalent ion substitution:Geometrical doping as a new doping route. Sci. Rep. 5, 10428 Summary of the Invention [Problem to be solved by the invention]

[0010] However, the n-type SnS described in Patent Document 1 is a sintered body and has a low activation rate, so 0.4 at% or more of Br must be added to exhibit n-type conductivity. Here, the activation rate refers to the ratio indicating how many carriers (conduction electrons and holes) the injected impurities emit. In addition, in the case of Patent Document 1, a spark plasma sintering method is used to obtain a sintered body. This method is for producing a bulk sample, and it is not possible to obtain a SnS thin film using the same method. The n-type SnS thin film described in Non-Patent Document 1 is made n-type by containing 20 at% or more of Pb, which results in a low activation rate. In addition, since it contains 20 at% or more of Pb, which is a harmful element, the advantage of SnS, which is to contain as few harmful elements as possible, is lost.

[0011] The present invention has been made in consideration of the above problems, and has an object to provide an n-type SnS thin film having a high impurity activation rate and exhibiting n-type conductivity, a photoelectric conversion element, a solar cell, a method for manufacturing an n-type SnS thin film, and an apparatus for manufacturing an n-type SnS thin film. [Means for solving the problem]

[0012] As a result of intensive research by the present inventors, it was found that the SnS thin film has a predetermined average thickness, an atomic ratio of the S content to the Sn content (S / Sn) that satisfies a certain relationship, and an absorption coefficient α 1.1 and the absorption coefficient α at photon energy 1.6 eV 1.6 It has been found that n-type conductivity is exhibited when the ratio of <1> The n-type SnS thin film according to one embodiment of the present invention has an average thickness of 0.100 μm to 10 μm. 、S The atomic ratio of the Sn content to the Sn content (S / Sn) is 0.85 to 1.10; Further comprising a dopant, The dopant is a halogen element, Absorption coefficient α at photon energy 1.1 eV 1.1 and the absorption coefficient α at photon energy 1.6 eV 1.6 The ratio of (α 1.1 / α 1.6 ) is less than or equal to 0.200, It has n-type conductivity. <2> the above <1> The n-type SnS thin film described in has an absolute absorption coefficient of 1.0×10 at a photon energy of 1.0 eV. 4 cm -1 It may be the following. <3> the above <1> or <2> The n-type SnS thin film described in the above contains 0.002 at % to 0.2 at % of the dopant. The above It may contain a halogen element. <4> the above <3> In the n-type SnS thin film described in 1. above, the halogen element may be at least one of Cl, Br, and I. <5> The photoelectric conversion element according to one aspect of the present invention includes the above <1> ~ <4> The present invention has a homo pn junction constituted by an n-type SnS thin film according to any one of the above items 1 to 4 and a p-type SnS thin film. <6> A solar cell according to one embodiment of the present invention comprises: <5> The photoelectric conversion element according to the present invention is <7> In a method for producing an n-type SnS thin film according to one embodiment of the present invention, an SnS thin film is formed by a vacuum film formation method in the presence of atomic S and a halogen element. <8> In the method for manufacturing an n-type SnS thin film according to <7> above, atomic S may be supplied by sulfur plasma. <9> In the method for manufacturing an n-type SnS thin film according to <7> above, atomic S may be supplied by H2S. <10> In the method for manufacturing an n-type SnS thin film according to any one of <7> to <9> above, before forming the SnS thin film, the manufacturing apparatus may be pre-supplied with a halogen element by irradiating a SnS target containing 5 at% to 15 at% of a halogen element with plasma. <11> In the method for manufacturing an n-type SnS thin film according to any one of <7> to <9> above, a halogen element may be supplied into the SnS thin film with a halogen gas. <12> In the method for manufacturing an n-type SnS thin film according to any one of <7> to <9> above, a SnS target containing 0.01 to 3 at% of a halogen element may be used for forming the SnS thin film to supply the halogen element. <13> The manufacturing apparatus for an n-type SnS thin film according to one aspect of the present invention uses the manufacturing method according to any one of <7> to <12> above.

Advantages of the Invention

[0013] According to the above aspect of the present invention, it is possible to provide an n-type SnS thin film, a photoelectric conversion element, a solar cell, a method for manufacturing an n-type SnS thin film, and a manufacturing apparatus for an n-type SnS thin film, which have a high activation rate of impurities and exhibit n-type conductivity.

Brief Description of the Drawings

[0014] [Figure 1] It is a schematic diagram of a sputtering apparatus. [Diagram 2] It is a diagram showing the XRD measurement results of the SnS thin film of the example and the X-ray diffraction pattern of SnS of the ICSD, and the SnS thin film of the comparative example.

Embodiments for Carrying Out the Invention

[0015] <n-type SnS thin film> The n-type SnS thin film according to this embodiment will be described below. The n-type SnS according to this embodiment has n-type conductivity. The SnS thin film is preferably mainly composed of SnS. "Mainly composed of SnS" means that only SnS is confirmed by X-ray diffraction analysis, and no other phases such as SnS2, Sn2S3, and SnO2 are confirmed. The SnS according to this embodiment may contain other phases such as SnS2, Sn2S3, and SnO2, as long as it exhibits n-type conductivity and achieves the effects of the present invention. In addition, it is preferable that the n-type SnS thin film according to this embodiment does not contain harmful elements as much as possible for safety.

[0016] "Average thickness is 0.100μm to 10μm" The average thickness of the n-type SnS according to this embodiment is 0.100 μm or more. More preferably, the average thickness of the n-type SnS is 1 μm or more. Even more preferably, the average thickness of the n-type SnS is 3 μm or more. When the average thickness of the n-type SnS is less than 0.100 μm, the light cannot be sufficiently absorbed. The average thickness of the n-type SnS is 10 μm or less. More preferably, the average thickness of the n-type SnS is 7 μm or less. Even more preferably, the average thickness of the n-type SnS is 4 μm or less. When the average thickness of the n-type SnS is more than 10 μm, there arises a problem that the light does not reach the vicinity of the homojunction interface, and a problem that the electrons and holes generated by the light irradiation cannot be taken out to the outside due to recombination.

[0017] "The atomic ratio of S content to Sn content (S / Sn) is 0.85 to 1.10." The atomic ratio (S / Sn) of the S content (at %) to the Sn content (at %) in the n-type SnS thin film of this embodiment is 0.85 to 1.10. If S / Sn is 0.85 to 1.10, the n-type SnS thin film can achieve a high activation rate.

[0018] The average thickness of n-type SnS can be measured by fluorescent X-ray analysis using the following method. For example, fluorescent X-rays of the n-type SnS thin film are measured using an X-ray fluorescent analyzer (e.g., MaXXi 5 manufactured by Matrix Metrologies). The average thickness of n-type SnS can be obtained from the obtained fluorescent X-rays by the fundamental parameter method.

[0019] "Absorption coefficient α at photon energy 1.1 eV 1.1 and the absorption coefficient α at photon energy 1.6 eV 1.6 The ratio of (α 1.1 / α 1.6 ) is 0.200 or less. The n-type SnS thin film according to this embodiment has an absorption coefficient α 1.1 and the absorption coefficient α at photon energy 1.6 eV 1.6 The ratio of (α 1.1 / α 1.6 ) is less than or equal to 0.200. 1.1 / α 1.6 When α is 0.200 or less, the SnS thin film exhibits n-type conductivity and the activation rate can be made 60% or more. More preferably, α 1.1 / α 1.6 is less than or equal to 0.100. 1.1 / α 1.6 may be 0.005 or more.

[0020] In the n-type SnS thin film according to this embodiment, the absolute value of the absorption coefficient at a photon energy of 1.0 eV is 1.0×10 4 cm -1 It is preferable that the absolute value of the absorption coefficient at a photon energy of 1.0 eV is 1.0×10 4 cm -1 The lower limit of the absolute value of the absorption coefficient at a photon energy of 1.0 eV is not particularly limited, but is preferably 1.0×10 3 cm -1 It may be more than that.

[0021] The absorption coefficient α of the SnS thin film can be measured, for example, by the following method. Using a spectrophotometer (for example, U4100 manufactured by Hitachi High-Technologies Corporation), the transmittance T (%) and reflectance R (%) of the SnS thin film at a measurement wavelength of 192 nm to 3200 nm are measured. By calculating from the following formula (1) using the obtained transmittance T, reflectance R, and average thickness t (cm) of the n-type SnS, the absorption coefficient α can be obtained. α = (1 / t) × ln((100 - R) 2 / (100 × T)) ···· (1)

[0022] "0.002 at% to 0.2 at% of halogen element" In the n-type SnS thin film according to this embodiment, the impurities for exhibiting n-type conductivity are not particularly limited. Examples of such impurities include halogen elements and Pb. The n-type SnS thin film according to this embodiment preferably contains 0.002 at% to 0.2 at% of a halogen element. If the halogen content is 0.002 at% to 0.2 at%, a sufficient carrier density can be obtained. As the halogen element, any one or more of Cl, Br, and I are preferable. In particular, as the halogen element, Cl and Br are preferable.

[0023] The content of impurities such as halogen elements in the n-type SnS thin film can be measured by a time-of-flight secondary ion mass spectrometer (for example, TOF-SIMS-5 manufactured by IONTOF-GmbH). For example, the depth profile of the halogen element in the n-type SnS thin film is measured using TOF-SIMS. In the obtained depth profile of the halogen element, in the range from the 1 / 4 position of the thickness of the n-type SnS thin film from the surface to the 1 / 2 position of the thickness of the n-type SnS thin film from the surface along the depth direction, the average value of the halogen element concentration in the region where the halogen element concentration is stable is taken as the content of the halogen element.

[0024] <Manufacturing method of n-type SnS thin film> Next, a method for producing an n-type SnS thin film will be described. In the method for producing an n-type SnS thin film according to this embodiment, an SnS thin film is formed by a vacuum film-forming method in the presence of atomic S and a halogen element. The method for forming the SnS thin film is not particularly limited as long as it is a vacuum film-forming method, and sputtering, vapor deposition, close-sublimation method, etc. can be used. The SnS thin film is preferably formed by sputtering. The manufacturing apparatus for the n-type SnS thin film is not particularly limited as long as the manufacturing method for the n-type SnS thin film according to this embodiment is used. When forming the film by sputtering, the film can be formed, for example, by a sputtering apparatus 100 as shown in FIG. 1.

[0025] The sputtering apparatus 100 shown in FIG. 1 includes a sputtering cathode 1, an SnS target 2 on the sputtering cathode 1, a heater 4 for vaporizing solid S powder 3, a high-frequency coil (RF coil) 5 for converting vaporized S into plasma, and a chamber 10. When forming an SnS thin film 6 on a substrate 7 by sputtering, the SnS thin film 6 can be formed, for example, by the following method. Undoped SnS is prepared as the SnS target, Ar is used as the sputtering gas, and quartz glass is used as the substrate 7. The substrate temperature is set to 220° C. to 340° C., and the SnS thin film 6 is formed in the presence of atomic S8 and a halogen element (film formation rate 8 nm / min). Here, "in the presence of atomic S and a halogen element" means that atomic S and a halogen element are present in the region where the SnS thin film is formed. If the substrate temperature is in the range of 220° C. to 340° C., the formed SnS thin film 6 is likely to exhibit n-type conductivity, which is preferable.

[0026] <Halogen elements> In the method for producing an n-type SnS thin film according to the present embodiment, a halogen element is supplied to the film formation atmosphere. As long as the content of the halogen element in the n-type SnS thin film is 0.002 at% to 0.2 at%, the method for supplying the halogen element is not particularly limited. As a method for supplying the halogen element, the halogen element may be supplied by forming the n-type SnS thin film using an SnS target containing 0.01 at% to 3 at% of the halogen element. Also, before or during the formation of the n-type SnS thin film, a halogen gas may be directly supplied to the film formation atmosphere. The flow rate of the halogen gas is, for example, 0.01 to 5 sccm. Also, the halogen element may be supplied to the film formation atmosphere by irradiating a plasma onto an SnS target containing the halogen element before the formation of the n-type SnS thin film. The supply amount of the halogen element can be appropriately adjusted based on conditions such as the exhaust speed of the vacuum pump and the size of the chamber 10.

[0027] When applying plasma to an SnS target containing halogen elements, it is preferable to apply plasma to SnS containing 5 at% to 15 at% of halogen elements (doped SnS). By applying plasma to doped SnS before film formation, a small amount of halogen elements (e.g., Cl) is left in the manufacturing apparatus (chamber 10), and halogen can be supplied to the atmosphere in advance during the subsequent film formation. This allows the concentration of halogen elements in the n-type SnS thin film to be controlled in the range of 0.002 at% to 0.2 at%.

[0028] <Atomic S> In the method for manufacturing an n-type SnS thin film according to this embodiment, atomic S8 is supplied to the film formation atmosphere. If S is simply vaporized and supplied, the vaporized S is in the form of clusters with low reactivity. Therefore, defects resulting from S vacancies in the SnS thin film 6 cannot be reduced. On the other hand, atomic S8 is more reactive than vaporized S, and can efficiently reduce defects resulting from S vacancies in the SnS thin film 6.

[0029] The method of supplying atomic S8 is not particularly limited, and for example, the solid S powder 3 may be heated, the vaporized S may be turned into a plasma state by the high-frequency coil 5, and then supplied to the deposition portion of the SnS thin film 6, or H2S gas may be supplied to the deposition portion of the SnS thin film 6. When H2S gas is used, it may be turned into a plasma state by the high-frequency coil 5 and then supplied to the deposition portion of the SnS thin film 6.

[0030] Next, a method of supplying the solid S powder 3 after turning it into a plasma state (S plasma) will be described. For example, the solid S powder 3 can be turned into a plasma state by the following method. The solid S powder 3 is heated at 75° C. to vaporize the solid S powder 3. The vaporized S is turned into a plasma state by the high-frequency coil 5, and atomic S8 is supplied. The power of the high-frequency coil 5 at this time is about 10 to 100 W, and the flow rate of the argon gas supplied to the high-frequency coil 5 is, for example, 1 to 20 sccm. Supplying Ar gas is preferable because it stabilizes the plasma. Conditions such as the power of the high-frequency coil 5 and the flow rate of the argon gas can be appropriately adjusted depending on the size of the chamber 10, etc.

[0031] A method for supplying H2S gas will be described. H2S is easily decomposed, and can efficiently reduce defects resulting from S deficiency in the SnS thin film 6. The flow rate of H2S gas is preferably 0.01 to 10 sccm. The flow rate of H2S gas can be appropriately adjusted based on conditions such as the exhaust speed of the vacuum pump and the size of the chamber 10. In order to further improve the reactivity of H2S, it may be made into a plasma state in the same manner as the solid S powder 3.

[0032] The n-type SnS thin film according to this embodiment has been described in detail above. The present invention is not limited to the specific embodiment, and various modifications and changes are possible within the scope of the present invention described in the claims. The n-type SnS thin film according to this embodiment can be used in a photoelectric conversion element such as a solar cell. For example, a photoelectric conversion element including the n-type SnS thin film according to this embodiment may have a homo pn junction composed of the n-type SnS thin film according to this embodiment and a p-type SnS thin film. A solar cell including the n-type SnS thin film according to this embodiment may have a photoelectric conversion element having the above homo pn junction. EXAMPLES

[0033] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0034] (Example) In the sputtering chamber, a Cl-doped SnS target was irradiated with plasma to supply Cl into the chamber, and the Cl was left in the chamber to supply Cl to the film formation atmosphere in the subsequent film formation. Specifically, a SnS target containing 10 at% Cl was irradiated with plasma at a power of 40 W for 30 minutes using Ar (flow rate 10 sccm) as the sputtering gas to supply Cl into the chamber.

[0035] After Cl was supplied to the deposition atmosphere, a quartz glass substrate was placed in the chamber, and a SnS thin film was deposited on the quartz glass substrate by sputtering while irradiating the SnS thin film with S plasma to obtain the SnS thin film of the example. The sputtering was performed using undoped SnS as the target, Ar as the sputtering gas, a substrate temperature of 330°C, and a deposition rate of 8 nm / min.

[0036] The SnS thin film was irradiated with S plasma using a Sulfur Cracking Source manufactured by Oxford Applied Research, and was carried out as follows: Solid S powder was vaporized by heating it to 75°C with a heater. Next, the vaporized S was turned into plasma with a power of 50 W while supplying Ar at a flow rate of 6 sccm to the high-frequency coil, and the SnS thin film being formed was irradiated with S plasma.

[0037] (Comparative Example) In the sputtering chamber, a Cl-doped SnS target was irradiated with plasma to supply Cl into the chamber, and by leaving it behind, Cl was supplied to the film formation atmosphere in the subsequent film formation. Specifically, a SnS target containing 10 at% Cl was irradiated with plasma at a power of 40 W for 30 minutes using Ar (flow rate 10 sccm) as the sputtering gas, and Cl was supplied into the chamber.

[0038] After Cl was supplied into the chamber, a quartz glass substrate was placed in the chamber, and a SnS thin film was formed on the quartz glass substrate by sputtering to obtain a comparative example of a SnS thin film. The sputtering was performed using undoped SnS as the target, Ar as the sputtering gas, a substrate temperature of 330°C, and a film formation rate of 6 nm / min.

[0039] (X-ray diffraction analysis) The SnS thin film was identified by X-ray diffraction. X-ray diffraction was performed using a Bruker D8 Discover, and measurements were made on the SnS thin film of the example and the SnS thin film of the comparative example using the θ-2θ method. The results are shown in Figures 2(a) and (b). The X-ray diffraction pattern of SnS from ICSD is shown in Figure 2(c).

[0040] (film thickness measurement) The film thickness was measured using an X-ray fluorescence analyzer (MaXXi 5 manufactured by Matrix Metrologies). The average thickness of the SnS thin film was obtained by the fundamental parameter method from the X-ray fluorescence obtained by measuring the SnS thin film of the example and the SnS thin film of the comparative example. The obtained results are shown in Table 1.

[0041] (X-ray fluorescence analysis) The chemical compositions of the SnS thin films of the examples and the comparative examples were measured using an X-ray fluorescence analyzer (MaXXi 5 manufactured by Matrix Metrologies).

[0042] (Hall measurement) Using a Hall measurement system (RESITEST8300 manufactured by Toyo Corporation), the electrical conductivity, Hall coefficient, and electrical conductivity and Hall coefficient in the temperature range of 60K to 300K of the SnS thin film of the example and the SnS thin film of the comparative example were measured by the van der Pauw method. A gold thin film with a thickness of about 100 nm was used for the electrode. From these results, the conductivity type, carrier density, and mobility were evaluated. The obtained results are shown in Table 1.

[0043] (Optical absorption spectrum measurement) Using a spectrophotometer (e.g., Hitachi High-Technologies Corporation U4100), the transmittance T (%) and reflectance R (%) of the SnS thin film were measured at measurement wavelengths of 192 nm to 3200 nm. The transmittance T and reflectance R of the obtained SnS thin film at each photon energy and the average thickness t (cm) of the n-type SnS were used to calculate the absorption coefficient from the above formula (1) to obtain an absorption spectrum. From the obtained absorption spectrum, the absorption coefficient α of the SnS thin film of the example and the SnS thin film of the comparative example at a photon energy of 1.1 eV was calculated. 1.1 and the absorption coefficient α at photon energy 1.6 eV 1.6 The ratio of (α 1.1 / α 1.6 ) and the absolute value of the absorption coefficient at photon energy 1.0 eV α 1.0 The results are shown in Table 1.

[0044] (TOF-SIMS measurement) The content of halogen elements was measured by a time-of-flight secondary ion mass spectrometer (TOF-SIMS-5 manufactured by IONTOF-GmbH). Specifically, the depth profiles of S, Sn, and Cl of the SnS thin film of the example and the SnS thin film of the comparative example were measured using TOF-SIMS. In the obtained depth profile of halogen elements, the average value of Cl concentration was calculated in the range from a position 70 nm deep from the surface to a position 110 nm deep from the surface along the depth direction, and this was taken as the content of halogen elements. The obtained results are shown in Table 1.

[0045] [Table 1]

[0046] FIG. 2 shows the results of XRD measurement of the SnS thin film of the example. The horizontal axis indicates 2θ (°), and the vertical axis indicates X-ray intensity. FIG. 2(a) shows the results of measurement of the SnS thin film of the example, and FIG. 2(b) shows the results of measurement of the SnS thin film of the comparative example. All peaks in FIGS. 2(a) and (b) belong to SnS. As shown in FIG. 2, there were no heterophases such as SnS2, Sn2S3, or SnO2. From this, it was confirmed that the thin films of the example and comparative example were composed of SnS.

[0047] As shown in Table 1, the absorption coefficient α at photon energy of 1.1 eV 1.1 and the absorption coefficient α at photon energy 1.6 eV 1.6 The ratio of (α 1.1 / α 1.6 The SnS thin film of the embodiment, in which the absorption coefficient α at a photon energy of 1.1 eV was 0.200 or less, exhibited n-type conductivity. 1.1 and the absorption coefficient α at photon energy 1.6 eV 1.6 The ratio of (α 1.1 / α 1.6) exceeded 0.200, exhibited p-type conductivity. The activation rate of the SnS thin film of the example, calculated from the Cl concentration and carrier density, was 65%. Conventional n-type SnS had an activation rate of several percent or less, so it was found that the SnS thin film of the present embodiment can be made into an n-type semiconductor with an extremely low Cl concentration of 0.018 at%.

[0048] Since non-doped SnS semiconductors generally exhibit p-type, the n-type SnS semiconductor of the present invention exhibits n-type, making it possible to realize a homojunction. Therefore, the n-type SnS semiconductor of the present invention is useful for a photoelectric conversion element for a homojunction type SnS solar cell having a pn junction with a p-type non-doped SnS semiconductor. In addition, since the SnS semiconductor does not contain expensive and rare elements, it is also expected to be an inexpensive photoelectric conversion material. [Industrial Applicability]

[0049] The n-type SnS thin film of the present invention is expected to be used in photoelectric conversion elements, solar cells, etc., and therefore has high industrial applicability.

Claims

1. The average thickness is 0.100 μm to 10 μm, The ratio of the S content to the Sn content (S / Sn) is 0.85 to 1.10; The SnS thin film further includes a dopant, the dopant being a halogen element, the ratio (α 1.1 / α 1.6 ) of the absorption coefficient α 1.1 at a photon energy of 1.1 eV to the absorption coefficient α 1.6 at a photon energy of 1.6 eV is 0.200 or less, and the material has n-type conductivity; N-type SnS thin film.

2. The absolute value of the absorption coefficient at a photon energy of 1.0 eV is 1.0 x 10 4 cm -1 2. The n-type SnS thin film of claim 1, wherein:

3. 3. The n-type SnS thin film according to claim 1, wherein the halogen element is contained in an amount of 0.002 at % to 0.2 at % as the dopant.

4. 4. The n-type SnS thin film according to claim 3, wherein the halogen element is at least one of Cl, Br, and I.

5. 5. A photoelectric conversion element having a homo pn junction composed of the n-type SnS thin film according to claim 1 and a p-type SnS thin film.

6. A solar cell comprising the photoelectric conversion element according to claim 5.

7. In the presence of atomic S and halogen elements, A method for producing an n-type SnS thin film, in which the SnS thin film is formed by a vacuum film formation method.

8. The method for producing an n-type SnS thin film according to claim 7, wherein atomic S is supplied by sulfur plasma.

9. H 2 The method for producing an n-type SnS thin film according to claim 7 , wherein atomic S is supplied by S.

10. The method for producing an n-type SnS thin film according to any one of claims 7 to 9, wherein, before forming the SnS thin film, a SnS target containing 5 at% to 15 at% of a halogen element is irradiated with plasma to supply a halogen element into a production device in advance.

11. The method for producing an n-type SnS thin film according to any one of claims 7 to 9, wherein a halogen element is supplied into the SnS thin film by a halogen gas.

12. The method for producing an n-type SnS thin film according to any one of claims 7 to 9, wherein a halogen element is supplied by using a SnS target containing 0.01 at % to 3 at % of a halogen element for depositing the SnS thin film.

13. An apparatus for producing an n-type SnS thin film using the method according to any one of claims 7 to 12.

Citation Information

Patent Citations

  • N-TYPE SnS SEMICONDUCTOR AND SOLAR CELL USING THE SAME

    JP2019178012A

  • Horizontal support device for radioactive substance storage container and horizontal support method for radioactive substance storage container

    JP2019179012A